Outcome and upper extremity function within 72 hours after first occasion of stroke in an unselected population at a stroke unit. A part of the SALGOT study - Persson, Hanna C (BioMed Central, 2012)
BACKGROUND: Reduced upper extremity function is one of the most common impairments after stroke and has previously been reported in approximately 70-80% of patients in the acute stage. Acute care for stroke has changes over the last years, with more people being admitted to a stroke unit as well as use of thrombolysis. The aim of the present study was to describe baseline characteristics, care pathway and discharge status in an unselected group of patients with first occasion of stroke who were at a stroke unit within 72 hours after stroke and also to investigate the frequency of impaired arm and hand function. A second aim was to explore factors associated with impaired upper extremity function and the impact of impairment on the patient’s outcome. METHODS: Patients over 18 years of age with first ever stroke, living in a geographical catchment area, being at the stroke unit within 72 hours after onset, with no prior upper extremity impairment were included. Baseline characteristics, arm and hand function within 72 hours, stroke outcome and care pathway in the acute phase were described, by gathering information retrospectively from the patients’ charts. Ischemic strokes were categorized according to the Bamford classification and the Trial of Org 10172 in Acute Stroke Treatment criteria. RESULTS: Of the 969 patients with first ever stroke who were screened, 642 patients fulfilled the inclusion criteria. According to the National Institutes of Health Stroke Scale (NIHSS), the patients had a mean score of 6.0, median 3.0, at arrival to the hospital. Ischemic stroke was most frequent in the anterior circulation (87.7%). Within 72 hours after stroke onset 48.0% of the patients had impaired arm and hand function and this was positively associated with higher age (p < 0.004), longer stay in the acute care (p < 0.001) and mortality in acute care (p < 0.001). Directly admitted to the stroke unit were 89.1% of the patients and 77.1% received hospital care on same day as stroke onset. Mean length of stay in the stroke unit was 9.9 days, 56.8% of the patients were discharged directly home from the stroke unit. Mortality within 72 hours after stroke onset was 5.0%. CONCLUSION: Impaired arm and hand function is present in 48% of the patients in a non selected population with first ever stroke, estimated within 72 hours after onset. This is less than previously reported. Impaired arm and hand function early after stroke is associated with higher age, longer stay in the acute care, and higher mortality within the acute hospital care.